Exam preparatory course for the 2nd part of the German medical examination in obstetrics and gynecology - a potential tool for the recruitment of new residents during the occupational decision process before the practical year? - Riedel, Fabian; Freis, Alexander; Heil, Jörg; Golatta, Michael; Schütz, Florian; Sohn, Christof; Hennigs, André (BMC medical education, 2019)
The “Second Stage of the Physician Exam” at the end of the 5th year of medical school in Germany is the final step before the “Practical Year.” An exam preparatory class can cover the complete content of Obstetrics and Gynecology (OB/GYN) in two days. We raise the question of whether such training might promote students’ interest in the given specialty during occupational decision making and whether it could even be used by hospitals as a recruitment tool. This investigation is even more important in the context of fierce competition among young professionals at clinics and in different specialties.
Gesehen am 24.01.2019